2023
DOI: 10.1108/jiabr-07-2023-0235
|View full text |Cite
|
Sign up to set email alerts
|

Developing employee motivation index: McClelland and Maqasid Shariah

Hamdy Abdullah,
Fahru Azwa Md Zain,
Sheikh Ahmad Faiz Sheikh Ahmad Tajuddin
et al.

Abstract: Purpose Many scholars have primarily disregarded employee motivation in the context of Western and Islamic ideas. To better understand employee motivation, this paper aims to explore a novel approach of fusing McClelland’s needs theory (i.e. achievement, power and affiliation) with Maqasid Shariah. Design/methodology/approach This study adopts a theoretical research design. There will be a thorough literature study of McClelland’s theory, Maqasid Shariah, and employee motivation. Qualitative content analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…This conceptual research proposes a novel integration of ESG principles with Maqasid al-Shariah within the framework of Takaful operations (Abdullah et al , 2023; Tahir et al , 2021). The research strategy and technique used for this study are described in this section.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This conceptual research proposes a novel integration of ESG principles with Maqasid al-Shariah within the framework of Takaful operations (Abdullah et al , 2023; Tahir et al , 2021). The research strategy and technique used for this study are described in this section.…”
Section: Methodsmentioning
confidence: 99%
“…The existing literature, principles and concepts of ESG principles and Maqasid al-Shariah within Takaful operations are analysed. Through this process, pre-determined themes or measurements based on established theories and frameworks suggested by scholars such as Haji Wahab and Mohamed Naim (2023), Abdullah et al (2023) and others (Agustin et al, 2023;Dirie et al, 2023;Harahap et al, 2023; IMEFM 17,3 Marwan et al, 2020;Shahid et al, 2023) are identified. These themes or measurements serve as a foundation for the conceptual framework.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, this aspect needs to be reexamined, whether it greatly affects the relationship between Mach and RtC or not. From many existing motivation theories, McClelland's Theory of Needs has been proven to be considerably applied in empirical studies to describe why people invest their time in a particular activity (Abdullah et al, 2023). However, there have not been many studies that investigate the relationship between RtC and all aspects of manifest needs.…”
Section: Introductionmentioning
confidence: 99%
“…By examining this correlation empirically and analyzing the data over a specific time frame (2006 to 2022), this study aims to provide valuable insights into how advancements in education can stimulate economic progress in the region. These insights will serve as a basis for formulating targeted policies and initiatives that can contribute to a more developed Terengganu, ultimately playing a role in the broader economic prosperity of the nation (Abdullah et al, 2023). This paper aims to analyze the nexus between educational achievements and economic development within Terengganu, considering the imperatives set forth by the Sustainable Development Goals (SDGs).…”
mentioning
confidence: 99%